(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The notion of this research is to implement of Kotaku Tanpa Kumuh program (KOTAKU) how is the accuracy of the KOTAKU program in achieving the program, so the program can create the livable of residential urban and the slum in the city 0%. This research uses quantitative research with descriptive approach, the type of research used in this research is inductive phenomology research type, data analysis used is, data reduction, data presentation, and conclusion drawing. The data in this research taken from ten informants. Technique of data collecting was deep interview, direct observation, and take documentation. The result of this research showed that the implementation of Kotaku Tanpa Kumuh program (KOTAKU) in District Bone has been accordance with Law No 01th of 2011 as one of the program of the slum areas arrangement in Sub-District Tanete Riattang, but it did not go well, where there were still people who complained about the inequality of infrastructure development in the slums tha caused social jealousy to accur, and the condition of the environment that still did not look healthy.